Incumbent innovation and entry by spinoff - Oliver Falck; Stephan Heblich (Friedrich Schiller University Jena and Max Planck Institute of Economics, 2008)
This paper takes a different perspective toward the escape entry incentive of incumbent firms to innovate. New entrants spawned from incumbents are not necessarily a threat; they can complement incumbents' production by commercializing knowledge incumbents are not willing or able to exploit. Accordingly, incumbent innovation determines exploitable knowledge externalities for spinoffs while, at the same time, spinoffs are expected to influence incumbent innovation. To overcome this problem of endogeneity, we apply an IV approach to analyze a rich industry-level dataset (19872000) for Germany. We find evidence that entry by spinoffs does, indeed, have a positive impact on incumbent innovation.
Keywords: O3; L16; M13; 330; Innovation; entry; spinoff; Betriebsaufspaltung; Unternehmensgründung; Innovationswettbewerb; Theorie; Deutschland